Virtual reality - Witte, K.; Pastel, S.; Bürger, D.; Petri, K. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
The chapter deals with possibilities of using VR in sports training. Mostly wireless HMDs are used today. VR makes it possible to simulate many sport-specific situations, so that the athlete can train his/her sport independent of location and time and under different conditions. In particular, VR tools are suitable for sports specific training reaction and anticipation skills in combat and game sports, and for learning or optimizing movement techniques. A specific advantage of VR training tools is the ability to train injury-free due to the simulation possibility. A future challenge is to develop teammates and opponents as "intelligently" as possible. Further technical developments focus on an enlarged field of view of the HMD and even better spatial and temporal resolution.